Effect of Micro-Pile Mitigation on Seismic Performance of Liquefiable Ground - Asokawati, Fajrina Citra; Fansuri, Muhammad Hamzah; Chang, Muhsiung; Lin, Hseu-Jen; Purwanti, Nina; Putra, Okri Asfino; Saputra, Pungky Dharma; Laksmi, Anasya Arsita (Department of Civil and Environmental Engineering, Faculty of Engineering, Universitas Gadjah Mada, 2024)
Soil liquefaction and its associated ground failures, pose a significant threat, causing damage to engineering structures during earthquakes, and one of the most effective methods used to mitigate liquefaction in liquefied soil is micro-pile (MP) method. Therefore, this study aims to examine the current state of MP method as liquefaction countermeasure in the soil of the Coal Fired Power Station in Central Java, an area with a high liquefaction potential. A three-dimensional finite element analysis, conducted with OpenseesPL software, uses a numerical method to yield information about ground lateral deformation and excess pore pressure generation caused by MP method during seismic shaking. This result examines important design parameters, including diameter, spacing, length of MP, and inclination of ground, to address these issues. MP method increases the stiffness of soil, reducing excessive pore pressure and thereby minimizing liquefaction risks. In general, MP remediation appeared effective for any sloping ground. This study provides valuable information for devising an efficient remediation solution by comparing relevant variables, such as diameter, spacing, MP length, and ground inclination, under the same conditions. Numerical simulation with OpenseesPL yields results such as stress and strain path, acceleration time histories, excess pore pressure, displacement time histories, and maximum lateral displacement, which are then compared with various diameter parameters. The diY6-ameter parameters were compared to test how the additional diameter dimension affects the performance of the micropile provided to the soil. This will be demonstrated based on the results shown on excess pore pressure and maximum lateral displacement. This comparison shows that increasing MP diameter is more effective in reducing the risk of liquefaction.